2019
DOI: 10.9734/ajpas/2019/v4i430122
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Micropolar Nanofluid Flow over an Inclined Surface by Means of Keller-Box

Abstract: In this paper, micropolar nanofluid boundary layer flow over a linear inclined stretching surface with the magnetic effect is investigated. Buongiorno’s model utilized in this study for the thermal efficiencies of the fluid flow in the presence of Brownian motion and thermophoresis properties. The nonlinear problem for micropolar nanofluid flow over an inclined sheet is established to study the heat and mass exchange phenomenon by considering portent flow parameters to strengthen the boundary layers. The gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…The same effect is seen in the case of angular velocity for changed values of M in Figure 5. The angular velocity shows an inverse relation with the magnetic field strength, which matches with the result of Rafique et al [31]. It is noticed in Figure 6 that f (η) increases with the increment of K. The angular velocity profile upsurge corresponding with higher magnitudes of K is indicated in Figure 7, and it emulates the result of Rafique et al [31].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The same effect is seen in the case of angular velocity for changed values of M in Figure 5. The angular velocity shows an inverse relation with the magnetic field strength, which matches with the result of Rafique et al [31]. It is noticed in Figure 6 that f (η) increases with the increment of K. The angular velocity profile upsurge corresponding with higher magnitudes of K is indicated in Figure 7, and it emulates the result of Rafique et al [31].…”
Section: Resultssupporting
confidence: 86%
“…Srinivasacharya et al [26] explored the double diffusive effect on the flow of micropolar fluid on a slanted sheet. Other similar studies on the different aspects of fluids are given in [27][28][29][30][31]. The flow symmetry of fluids in general has been studied using theoretical methods, various experiment methods, and different numerical techniques, in various fields such as the field of fluid mechanics, the field of thermal engineering, etc., due to their several benefits and relevance in terms of flow control and heat transfer enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…where u w = cx is the velocity of sheet and c is the constant, α f is the thermal diffusivity, τ w is the ratio of effective heat capacity, v 0 is the suction/injection parameter, C ∞ and T ∞ are the ambient concentration and temperature respectively, such that T f > T ∞ and C w > C ∞ . Following similarity will be used to get similarity solution of Equations (7)-(10) with subject to boundary conditions Equation (11). Moreover, m is the constant, where m = 0 which means that microelements are unable to rotate, when = 0.5 which implies that antisymmetric part of the stress tensor is vanishing and where m = 1 which indicates the model of the turbulent flow.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Recently, micropolar nanofluid in the presence of magnetic force was investigated by Patel et al [10] in which they also noticed a single solution. Rafique et al [11] considered micropolar nanofluid on the inclined stretching plane where they obtained a single local similarity solution. Moreover, they claimed that the effect of the Brownian motion is then inversely proportional to the rate of heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of dual dispersion on micropolar liquid flow over a slanted surface was discussed by Srinivasacharya et al [31]. Recently, Rafique et al [32] probed the energy and mass transport of micropolar nanofluid flow over an inclined stretching surface. They found that the velocity profile diminishes with the increment in the inclination and magnetic effect.…”
Section: Introductionmentioning
confidence: 99%